Kreasi sabun kopi sereh jeruk sebagai inovasi baru bagi konsumen: Creation of coffee lemongrass orange soap as a new innovation for consumers - Lisnani, Lisnani; Tanujaya, Benidiktus; Sopian; Elsye Purnama Sari , Agnes; Eliana, Ribka; Florensia, Monica; Alfredo, Kevien; Aldi Renaldi , Oktavianus Aldi (Fakultas Peternakan Universitas Papua, 2024)
ABSTRACT The initial idea of ​​the PKM team came from the community's need for soap and the benefits of soap for the community. Soap is a daily necessity in people's lives, not only for cleaning but also to provide a unique aroma for the body. The variants and forms of soap circulating in the community that are still limited provide their own inspiration for this community service activity. This is what makes the team innovate and create natural soap. The purpose of this PKM activity is to produce a product in the form of natural soap from coffee, lemongrass, and orange which is given the KOSERUK brand with 5 different variants. The method of implementing this PKM activity consists of aspects of production, business management in the form of product branding and marketing strategies, product manufacturing techniques, packaging, and marketing. The results of this community service activity are soap with 5 different variants given the KOSERUK brand as many as 500 bars of soap that are marketed to the community. In the future, this KOSERUK soap is expected to be the community's choice. Keywords: Creation; Coffee; Lemongrass; Orange; Soap ABSTRAK Ide awal tim PKM berawal dari kebutuhan masyarakat terhadap sabun dan kebermanfaatan sabun bagi masyarakat. Sabun merupakan kebutuhan sehari-hari dalam kehidupan Masyarakat tidak hanya untuk membersihkan tetapi juga untuk memberikan aroma tersendiri bagi tubuh. Varian dan bentuk sabun yang beredar di masyarakat yang masih terbatas memberikan inspirasi tersendiri bagi di dalam kegiatan pengabdian ini. Inilah yang membuat tim berinovasi dan berkreasi memproduksi sabun berbahan alami. Tujuan kegiatan PKM ini adalah menghasilkan produk berupa sabun berbahan alami dari bahan kopi, sereh dan jeruk yang diberi merek KOSERUK dengan 5 varian berbeda. Metode pelaksanaan kegiatan PKM ini terdiri dari aspek produksi, manajemen usaha berupa branding produk dan strategi pemasaran, teknik pembuatan produk, pengemasan dan pemasaran. Hasil dari kegiatan pengabdian ini berupa sabun dengan 5 varian berbeda yang diberi merek KOSERUK sebanyak 500 batang sabun yang dipasarkan kepada masyarakat. Sabun KOSERUK ini kedepannya diharapkan bisa menjadi pilihan masyarakat. Kata kunci: Jeruk; Kreasi; Kopi; Sabun; Sereh